Moral leadership for a divided age : fourteen people who dared to change our world - Gushee, David P., 1962-; Holtz, Colin, 1985- (Brazos Press; Grand Rapids., 2018)
"Examines the lives of great leaders of recent centuries to offer models of moral leadership, helping readers discover lessons for their own lives and times"--
Moral leaders time line -- The study of moral leadership -- William Wilberforce 1759-1833 -- Abraham Lincoln 1809-65 -- Harriet Tubman 1822?-1913 -- Florence Nightingale 1820-1910 -- Ida B. Wells-Barnett 1862-1931 -- Mohandas Gandhi 1869-1948 -- Dietrich Bonhoeffer 1906-45 -- Mother Teresa 1910-97 -- Oscar Romero 1917-80 -- Nelson Mandela 1918-2013 -- John Paul II 1920-2005 -- Elie Wiesel 1928-2016 -- Martin Luther King Jr. 1929-68 -- Malala Yousafzai 1997- -- Daring to change our world.
Includes bibliographical references and index.
Keywords: Leadership -- Moral and ethical aspects; Role models -- Biography; Biographies